Electrode Kinetic Studies of the Hydroquinone-Benzoquinone System and the Reaction between Hydroquinone and Ammonia in Propylene Carbonate: Application to the Indirect Electroanalytical Sensing of Ammonia - Ji, X.; Banks, C.; Silvester, Debbie; Wain, A.; Compton, R. (American Chemical Society, 2007)
The oxidation of hydroquinone and reduction of benzoquinone have been studied by cyclic voltammetry at glassy carbon electrodes in propylene carbonate. Diffusion coefficients of the different species obtained from chronoamperometric measurements with use of microdisk electrodes were 2.7 ( 0.3 X 10-6 cm2 s-1 for hydroquinone and 4.2 ( 0.2 X 10-6 cm2 s-1 for benzoquinone. Simulation was used to model the cyclic voltammetric responses of macroelectrodes to give electrode kinetic information for the electrochemical oxidation of hydroquinone and reduction of benzoquinone. Next, the reaction between ammonia and hydroquinone was investigated. It is shown that ammonia reversibly removes one proton from the hydroquinone molecules, resulting in a new wave observed at ca. + 0.15 V (vs Ag wire). Finally by measuring the peak current of the new wave as a function of ammonia concentration its analytical utility for ammonia sensing was examined in the range from 10 and 100 ppm.